2010
DOI: 10.1103/physrevb.81.104411
|View full text |Cite
|
Sign up to set email alerts
|

Spin dynamics in the geometrically frustrated multiferroicCuCrO2

Abstract: The spin dynamics of the geometrically frustrated triangular antiferromagnet multiferroic CuCrO 2 have been mapped out using inelastic neutron scattering. The relevant spin Hamiltonian parameters modelling the incommensurate modulated helicoid have been determined, and correspond to antiferromagnetic nearest and next-nearest neighbour interactions in the ab plane, with a strong planar anisotropy. The weakly dispersive excitation along c reflects the essentially two-dimensional character of the magnetic interac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
84
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 21 publications
12
84
0
2
Order By: Relevance
“…Figure 3-(d-i) shows χ ′′ (Q, E) at low Q zooming on magnetic excitations (12 meV data). As one can observe, the magnetic intensity extends from 0 to 15 meV for Q < 5Å −1 , and remains visible up to 300 K, far above T N ≃ 24 K. Even the 55 meV data measured at 530 K show some remnant magnetic intensity at low Q , see Figure 3-f. A similar observation was also reported by Poienar et al [9], but their measurements were limited to low temperatures (T ⩽ 40 K). We show the temperature dependence of magnetic intensity between 2.25 ⩽ E ⩽ 11 meV in Fig 8-d.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Figure 3-(d-i) shows χ ′′ (Q, E) at low Q zooming on magnetic excitations (12 meV data). As one can observe, the magnetic intensity extends from 0 to 15 meV for Q < 5Å −1 , and remains visible up to 300 K, far above T N ≃ 24 K. Even the 55 meV data measured at 530 K show some remnant magnetic intensity at low Q , see Figure 3-f. A similar observation was also reported by Poienar et al [9], but their measurements were limited to low temperatures (T ⩽ 40 K). We show the temperature dependence of magnetic intensity between 2.25 ⩽ E ⩽ 11 meV in Fig 8-d.…”
Section: Resultssupporting
confidence: 70%
“…Thus, it presents an opportunity to study the direct coupling between the magnetic and ferroelectric order parameters [3,4]. A number of studies have investigated the crystal structure, magnetic excitations, magnetization, and electric polarization in CuCrO 2 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], but little is known about the phonons and their coupling or response to the magnetic/ferroelectric ordering.…”
Section: Introductionmentioning
confidence: 99%
“…The cause of the incommensurability of the propagation vector has been discussed earlier, and two different explanations have been proposed: either an inplane lattice distortion [4,5] or interlayer exchange interaction [20][21][22][23]. The latter is in better agreement with the occurrence of 3-dimensional order, although it had been shown that an interlayer exchange has to be relatively small (<0.2meV) [24]. The maximum ordered moment in our model is 2.8(2) µ B which is close to the expected 3 µ B for the Cr 3+ ion and the reported values from the powder measurements [10,11].…”
Section: Discussionmentioning
confidence: 91%
“…However, precise numerical calculations for the spin-1=2 TLHAF, which take into account nearest-neighbor interactions only [24][25][26], indicate that quantum fluctuations are not enough to suppress magnetic ordering and the actual ground state is a noncollinear long-range ordered spin structure. Experiments on various spin-S triangular-lattice antiferromagnets have overwhelmingly confirmed this picture [27][28][29][30], with a few noteworthy exceptions [31][32][33]. Several perturbations from the pure TLHAF have been proposed to enhance quantum fluctuations: next-nearest neighbor (NNN) interactions [34][35][36][37][38], ring-exchange terms [39,40], and anisotropic exchange [41][42][43][44], although it remains theoretically unclear if the latter mechanism alone can stabilize a QSL [45][46][47][48].…”
Section: Introductionmentioning
confidence: 98%